2018
DOI: 10.1007/s10120-018-0893-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life and nutrition status of the aboral pouch reconstruction after total gastrectomy for gastric cancer: a prospective multicenter observational study (CCOG1505)

Abstract: Background Several efforts have been made to alleviate harms and symptoms after gastrectomy for gastric cancer. We previously conducted a randomized controlled trial (CCOG1101) to compare quality of life (QOL) and nutritional status between Roux-en-Y (RY) and aboral pouch (AP) reconstructions for up to 1 year after total gastrectomy. However, long-term outcomes after AP reconstruction remain unclear. Methods A prospective multicenter observational study was conducted to compare QOL, body composition, and nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
1
35
0
2
Order By: Relevance
“…Weight gain was statistically significant in 5 studies (11,12,16,19,20) and statistically insignificant in 9 studies (13,14,15,17,18,21,22,24,25). 5 studies (11,12,16,19,20) reported a significant weight gain in the pouch group compared to simple eso-jejunostomy, and no differences were found in 5 studies (14,15,17,22,25). In the group that compared the Rouxen-Y with the jujunal interposition, only two study (12,20) reported a significant weight gain, while 5 studies (13,18,21,24) found no significant differences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Weight gain was statistically significant in 5 studies (11,12,16,19,20) and statistically insignificant in 9 studies (13,14,15,17,18,21,22,24,25). 5 studies (11,12,16,19,20) reported a significant weight gain in the pouch group compared to simple eso-jejunostomy, and no differences were found in 5 studies (14,15,17,22,25). In the group that compared the Rouxen-Y with the jujunal interposition, only two study (12,20) reported a significant weight gain, while 5 studies (13,18,21,24) found no significant differences.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the quality of life between studies was difficult, as six types of indicators were used (Visick, Spitzer, QLQ-C30, GSRS (Gastrointestinal Symptom Rating Scale), Cushieri and institutional questionnaires). The QLQ-C30 questionnaire was used in 4 studies (18,22,23,25), GSRS questionnaire in two studies (17,19), Cushieri questionnaire (15) in one study, and nonstandardizated questionnaires in 6 studies (11,14,16,20,21,24). The quality of life was assessed with the Visick scale in a single study (13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase is attributed to early detection and the development of treatment. In addition, quality of life and nutritional management may affect the survival rate of patients who undergo gastric cancer surgery [ 3 ].…”
Section: Introductionmentioning
confidence: 99%